The Value of Incorporating Measures of Relationship Concordance When Constructing Profiles of Intimate Partner Homicides: A Descriptive Study of IPH Committed Within London, 1998-2009. Issue 10 (May 2017) - Sebire, Jacqueline
This article presents a profile of intimate partner homicides (IPH) committed within London incorporating a gendered comparison of the perpetrators' relationships. Data was sourced from the original police files for offenses committed in the capital between 1998 and 2009 ( N = 207; 173 male and 34 female perpetrators). In common with other international descriptive studies, the results indicate comparative differences between partners according to perpetrator gender in terms of age profiles, employment status, experience of mental health issues, intoxication at time of killing, and possession of criminal convictions. Gender-based IPH descriptive studies have tended to focus on a collation of either victim or perpetrator or relationship characteristics, often in isolation from one another. Assessments of how parties interact within fatal relationships are invariably absent, and yet, it is the relationship that forms the backdrop against which the fatal acts are perpetrated. This study, therefore, not only provides an insight into the profile of IPH committed within London where none had previously existed but also demonstrates the advantages of incorporating relationship concordance measures. The inclusion of such measures when researching IPH assists homicide investigators in understanding the dynamics taking place within the cohort of fatal relationships they police. It also provides researchers a useful platform to enhance understanding of this crucial aspect, for it is the relationship itself which is what defines IPH and distinguishes as a unique subset of homicide.